The bad, the ugly and the monster behind the mirror - Food insecurity, mental health and socio-economic determinants - Aguiar, Ana; Pinto, Marta; Duarte, Raquel (Journal of psychosomatic research, 2022)
Food insecurity is associated with poor mental health outcomes, including depression and anxiety and COVID-19 could increase these relations. In this sense, we aimed to explore the relationship between food insecurity and mental health features and behaviors in adults from Portugal. We conducted a cross-sectional online snowball study from November 2020 until February 2021. A total of 882 Portuguese residents 18 years of age or older with food security data were included. Data on socio-demographics, food security status, and anxiety and depression symptoms were collected. Crude and adjusted logistic regression models were performed. Odds ratio (OR) and respective 95% confidence intervals (CI) were estimated. Most participants were women (71.3%), with a mean (SD) age of 36.8 (10.9) years, three-thirds had a university degree (76.7%), and 65.3% lived in the country's northern region. Regarding the characteristics associated with food insecurity, we observed that less-educated participants (OR = 7.84; 95% CI: 3.67–16.73), with depression symptoms (OR = 5.91; 95% CI: 3.12–11.19) and with anxiety symptoms (OR = 6.41; 95% CI: 3.02–13.59), had a higher odds of belonging to a food-insecure household. After adjustments less educated individuals (OR = 8.37; 95% CI: 3.81–18.35), those who faced a reduction in income (OR = 0.27; 95% CI: 0.13–0.53) and, presenting anxiety symptoms (OR = 7.32; 95% CI: 3.53–15.17) had a higher odds of belonging to a food-insecure household. Approaching food insecurity without addressing mental health, and the opposite is making partial and reductive interventions. It is important to have an integrative approach. •The risk of mental health crises increases during public health emergencies.•WHO advised about COVID-19 mental health consequences such as depression and anxiety.•Food insecurity is associated with poor mental health outcomes.•Less-educated with mental health symptoms present a higher odds of food insecurity.•These groups should be targeted to specific approaches to reduce the burden.